2021
DOI: 10.3389/fpsyg.2021.669907
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Selective Mutism in Non-clinical 3- to 6-Year-Old Children: Relations With Social Anxiety, Autistic Features, and Behavioral Inhibition

Abstract: Selective mutism (SM) is a psychiatric condition that is characterized by a failure to speak in specific social situations (e. g., at school) despite speaking normally in other situations (e.g., at home). There is abundant evidence that anxiety, and social anxiety in particular, is a prominent feature of SM, which is the main reason why this condition is currently classified as an anxiety disorder. Meanwhile, there is increasing support for the notion that autism-related problems are also involved in SM. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 80 publications
(109 reference statements)
5
7
1
Order By: Relevance
“…Second, besides a sample of nonclinical children (Sample 1), the present study also included clinically referred children with SM and children with other social-emotional psychopathology (Sample 2). In keeping with our previous study [28], we expected to find positive correlations between social anxiety, behavioral inhibition, and ASD symptoms on the one hand and symptoms of SM on the other hand. We also anticipated that social anxiety and ASD symptoms would each explain a unique and significant proportion of the variance in symptoms of SM, but that these variables would no longer make a significant contribution once the temperament trait of behavioral inhibition was added to the model [28].…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…Second, besides a sample of nonclinical children (Sample 1), the present study also included clinically referred children with SM and children with other social-emotional psychopathology (Sample 2). In keeping with our previous study [28], we expected to find positive correlations between social anxiety, behavioral inhibition, and ASD symptoms on the one hand and symptoms of SM on the other hand. We also anticipated that social anxiety and ASD symptoms would each explain a unique and significant proportion of the variance in symptoms of SM, but that these variables would no longer make a significant contribution once the temperament trait of behavioral inhibition was added to the model [28].…”
Section: Introductionsupporting
confidence: 81%
“…In keeping with our previous study [28], we expected to find positive correlations between social anxiety, behavioral inhibition, and ASD symptoms on the one hand and symptoms of SM on the other hand. We also anticipated that social anxiety and ASD symptoms would each explain a unique and significant proportion of the variance in symptoms of SM, but that these variables would no longer make a significant contribution once the temperament trait of behavioral inhibition was added to the model [28]. Finally, in the clinically referred children with SM, we anticipated not only higher levels of social anxiety and behavioral inhibition but also elevated levels of ASD symptoms.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Second, there are studies that have investigated the relationship between symptomatology of SM and various constructs assessed by validated questionnaires or interviews. Here, studies suggest the temperamental trait of behavioral inhibition (BI), which is expressed, for example, in terms of distress to novelty, shyness, and fear responses such as a strong inhibition in new environments or toward strangers [ 16 ], to be important in children with SM [ 17 , 18 ]. Furthermore, it has been consistently shown that children with SM have, on average, clinically relevant levels of social anxiety [ 8 ].…”
Section: Introductionmentioning
confidence: 99%